Blockchain technology and smart contract for civil structural health monitoring system. (7th May 2021) - Xu, Jie; Liu, Haoran; Han, Qinghua
Abstract: The rapid development of blockchain technology is exerting a profound impact on all walks of life. Blockchain, which is a decentralized and distributed technology architecture, has inspired people to think about the social development model. However, blockchain technology has not been applied to health monitoring. Therefore, this study proposes a distributed health monitoring system based on blockchain technology, which realizes data security, information transparency, efficient sharing, and independent decision making with smart contracts. First, the system is designed as a blockchain network for structural health monitoring (SHM), and a series of smart contracts for health monitoring is developed to achieve monitoring authority verification, structural damage identification, and other functions. Based on the strength of the Ethereum private chain and Guangzhou New TV Tower benchmark model, smart contracts for health monitoring were deployed, and a series of tests of the proposed system were performed. The results indicate that the proposed system can provide monitoring authority verification, generate abnormal alerts, immutability of data, attack resistance, and traceability query.